SOCIAL RISKS TO HUMAN DEVELOPMENT: ESSENCE AND PLACE IN PUBLIC ADMINISTRATION - Bulba V.H.; Yevtukhov O.V. (Pressing Problems of Public Administration, 2017)
The theoretical approaches, existing in the national and world science, to the de nition of the essential characteristics of social risk in terms of realistic and irrational perception are generalized. The main trends in transformation of the social risk concept in the modern Ukrainian society and civilization as a whole are determined. The author’s definition of social risk to human development in the public administration system has been formulated.